Comparison of intraosseous and submucosal dexamethasone injection in mandibular third molar surgery: a split-mouth randomized clinical trial - S. Kaewkumnert (2020)
© 2019 International Association of Oral and Maxillofacial Surgeons The objective of this study was to compare the effect of intraosseous dexamethasone injection and submucosal dexamethasone injection on postoperative sequelae after mandibular third molar surgery. This was a randomized, triple-blind, split-mouth clinical trial. Fifty-four mandibular third molars (27 patients) were subdivided according to the side (right and left); intraosseous injection of dexamethasone (4 mg) was randomly assigned to one side and submucosal injection to the other. All surgeries were performed by one surgeon. Postoperative pain was evaluated by visual analogue scale score immediately after surgery and on postoperative days 1, 3, and 7. Postoperative swelling (determined using two linear measurements) and mouth opening (determined by measurement of the inter-incisal distance) were assessed on postoperative days 3 and 7. The number of analgesics consumed was recorded. No significant difference in pain or swelling was found between the two injection techniques. However, there was significant difference in trismus on postoperative day 3, with submucosal injection showing a better outcome (P < 0.001). Both techniques of dexamethasone injection were effective in controlling pain and swelling after mandibular third molar surgery, but submucosal injection was superior for the control of trismus.